Selective reduction of NOx with C3H6 over Cu and Cr promoted CeO2 catalysts - Amin, Norsarahaida; Tan, Eng Fong; Manan, Z. A. (Elsevier Science B.V., 2003)

(untitled)
The Cu/CeO2 and Cu/Cr/CeO2 catalysts synthesized using the impregnation method were employed to investigate the selective reduction of NOx with C3H6 at 673.15 K and 1 atm. The activity of CeO2 was greatly induced by loading 4 wt.% of Cu onto the bare support. The presence of C3H6 was a crucial factor for elevating the NOx conversion under lean conditions. The modification of the optimal Cu(4)/CeO2 catalyst with 3 wt.% of Cr steadily improved the performance of the catalysts. Both the optimal Cu(4)/CeO2 and Cu(4)/Cr(3)/CeO2 catalysts were characterized using XRD, SEM and TPR-H2. The co-existence of CuO, Cr2O3 and CuCr2O4 was believed to grant the promising performance of the Cu(4)/Cr(3)/CeO2 catalyst in SCR-HC under net oxidizing conditions